2020
DOI: 10.1017/s1473550420000269
|View full text |Cite
|
Sign up to set email alerts
|

Expecting the unexpected in the search for extraterrestrial life

Abstract: On p. 10 of the 2018 National Academies Exoplanet Science Strategy document (NASEM 2018), ‘Expect the unexpected’ is described as a general principle of the exoplanet field. But for the next 150 pages, this principle is apparently forgotten, as strategy decisions are repeatedly put forward based on our expectations. This paper explores what exactly it might mean to ‘expect the unexpected’, and how this could possibly be achieved by the space science community. An analogy with financial investment strategies is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Several studies have found significant increases in pseudoscientific beliefs and psychopathological risks during the coronavirus pandemic ( Escolà-Gascón et al, 2020 ). Pseudoscientific beliefs are frequently irrational (e.g., believing in the existence of the Loch Ness monster), but they do not necessarily have to be magical (e.g., believing in the existence of intelligent extra-terrestrial life) (see Dagnall, Munley, et al, 2010 ; Dagnall, Parker, et al, 2010 ; Dagnall et al, 2011 ; Vickers, 2020 ; Escolà-Gascón, O’Neill, & Gallifa, 2021 ). In this latter example, the content is not magical because astrophysicists are looking for and finding a multitude of exoplanets (see the publication of Samland et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found significant increases in pseudoscientific beliefs and psychopathological risks during the coronavirus pandemic ( Escolà-Gascón et al, 2020 ). Pseudoscientific beliefs are frequently irrational (e.g., believing in the existence of the Loch Ness monster), but they do not necessarily have to be magical (e.g., believing in the existence of intelligent extra-terrestrial life) (see Dagnall, Munley, et al, 2010 ; Dagnall, Parker, et al, 2010 ; Dagnall et al, 2011 ; Vickers, 2020 ; Escolà-Gascón, O’Neill, & Gallifa, 2021 ). In this latter example, the content is not magical because astrophysicists are looking for and finding a multitude of exoplanets (see the publication of Samland et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…12 https://www.epa.gov/air-trends/nitrogen-dioxide-trends 13 This issue is effectively the same as the problem of "unconceived alternatives" encountered in the philosophy of science (Stanford 2006; see also Mill 1846, p. 296). This aspect, along with the aforementioned hurdle of determining priors, was articulated vis-à-vis ETIs by Vickers (2020) and Cowie (2021Cowie ( , 2023. may be lower for some technosignatures, which runs counter to the goal of maximizing this quantity to the extent feasible insofar as genuine technosignatures, and not spurious signals masquerading in this fashion, are concerned.…”
Section: Artifact Technosignaturesmentioning
confidence: 99%
“…It is also just generally good practice to respect the range of "risk tolerance" among practitioners in the field, and ensure that some fraction of our collective efforts are "high-risk, high-reward." (Loeb 2010;Vickers 2020) Note that this is a separate question from how one should manage media attention to particular claims, particularly sensationalized stories in the yellow press. A discussion of that particular problem is beyond the scope of this work, but I will summarize my recommendation here by repeating: engage experts, and plan for success.…”
Section: Stay Broad-mindedmentioning
confidence: 99%